The Influence of Product Innovation and Market Orientation on Competitive Advantage and Business Performance: An Empirical Study of Songkok Recca Craftsmen in Bone Regency - Nurfatwa Yasin; Alwi Sibali; Kurniawaty Kurniawaty; Afriyani Afriyani; Andi Tenri Uleng Akal (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Songkok Recca, a traditional craft from Bone Regency, South Sulawesi, holds significant cultural value and continues to be used in traditional ceremonies.In addition to its high quality and aesthetic value, this Songkok has commercial appeal in local, national, and international markets. This Songkok has long been one of the main sources of livelihood for a number of craftsmen in Bone. However, in facing the era of modernization, globalization, and increasingly tight market competition, not all traditional craftsmen are able to survive and thrive.Objective: to empirically test the influence of market orientation, product innovation and competitive advantage on the performance of the Recca songkok craftsmen's business in Bone Regency.Design/methodology/approach: This study employs a quantitative approach by distributing questionnaires to respondents. The population consists of all Recca Songkok craftsmen in Awampone District, Bone Regency, totaling 250 individuals. Sampling was carried out using inclusion criteria, resulting in a total sample of 200 respondents. The analysis technique used in this study is Structural Equation Modeling (SEM). Findings/Results: Directly, market orientation and product innovation have a positive and significant effect on competitive advantage. Product innovation also has a significant effect on business performance, while market orientation does not have a significant effect on business performance. Indirectly, both variables have a significant effect on business performance through competitive advantage.Conclusion: Market orientation and product innovation have a significant influence on the competitive advantage of Songkok Recca artisans in Bone Regency. Market orientation enables artisans to align products with consumer preferences, while product innovation enhances value creation and strengthens competitiveness. However, only product innovation has been proven to have a direct effect on improving business performance, while market orientation does not show a significant direct effect on business performance.Originality/value (State of the art): Market orientation has not had a significant impact on improving the performance of Recca songkok craftsmen in Bone Regency. Keywords: market orientation, product innovation, competitive advantage, business performance, Songkok Recca